Teams and learning in organizations - Edmondson, Amy C. (Henry Stewart Talks, 2013)
Teams and teaming, Collaboration in complex, uncertain environments, Leadership facing uncertainty, Effects of power and status, Psychological safety, Learning from mistakes, Speaking up, Framing, Developing people, Promoting innovation
Reviewed at 2018/11/28